The Nox1/Nox4 inhibitor attenuates acute lung injury induced by ischemia-reperfusion in mice - Cui, Yu (PLoS One, 2018)
Lung ischemia and reperfusion injury (LIRI) were mediated by several processes including over-production of reactive oxygen species (ROS) and inflammatory activation. ROS generated by nicotinamide adenine dinucletide phosphate (NADPH) oxidase (Nox) may play a pivotal role in pathophysiological changes in a range of disease. However, it was poorly understood in LIRI. Thus, the purpose of our study was to explore whether GKT137831, as a special dual inhibitor of Nox1 and 4, could alleviate LIRI in mice model and explore the minimal dose. According to the protocol, this study was divided into two parts. The first part was to determine the minimal dose of Nox1/4 inhibitor in attenuating LIRI via histopathology and apoptosis analysis. Eighteen C57BL/6J male wild-type mice were randomly divided in to sham, 2.5Nox+sham, 5.0Nox+sham, IR, 2.5Nox+IR and 5.0Nox+IR groups. According to the different group, mice were pretreated with corresponding dose of Nox1/4 inhibitors or normal saline. After LIRI, the results showed 5.0mg/kg Nox1/4 inhibitor could be considered as the minimal dose to alleviate injury by decreasing of lung injury score and the number of TUNEL-positive cells. The second part was to further verify the benefit of 5.0mg/kg Nox1/4 inhibitor in lung protective effects. Thirty-seven C57BL/6J male wild-type mice were divided in to sham, IR and 5.0Nox+IR groups randomly. The results showed that expressions of inflammatory, autophagy cytokines were markedly elevated and PH value was declined after LIRI. However, 5.0 mg/kg Nox1/4 inhibitor significantly attenuated cytokine production as reflected by immunohistochemistry, western blotting and Q-PCR analysis. In conclusion, our findings suggested that 5.0mg/kg Nox1/4 inhibitor contributed to protect lung tissue damage after LIRI via the suppression of inflammatory and autophagy activation.